Using Black Hole Environments as Laboratories for Testing Accretion and Gravity - Georgiev, Boris (University of Waterloo, 2023)
With the advent of the Event Horizon Telescope (EHT), we have the ability to observe the lensed emission from hot plasmas near event horizons. It contains entangled information about the turbulent magnetohydrodynamic accretion processes and the black hole spacetime. We present studies of both coherent and stochastic variable features measurable from EHT data, and by applying them to libraries of simulations, we describe how they inform on the underlying accretion flow. For a rapidly varying source like Sgr A*, we find that variability is greatest on the largest spatial scales and the longest timescale, and find a universal power-law variability prescription in the visibility domain. For a slowly varying source like M87*, we measure a correlation timescale and a rotation rate, which is inconsistent with the velocity of the fluid causing the emission. The strong predictions from the simulations of the variability measures we create are consistent with current EHT data. We also create a static analytical midplane accretion flow model and use variable simulations to motivate a prescription to incorporate turbulent effects. Our model matches SANE models well and struggles with the more variable MAD models. It can incorporate non-Kerr metrics, can connect the black hole scales to their large-scale environment, and can be incorporated in existing parameter estimation frameworks to fit EHT data.
Keywords: black holes; magnetohydrodynamics; image analysis; fluids; interferometry; plasma physics